Implementasi Kerahasiaan Medis dalam Penanganan Kasus HIV/AIDS di Lembaga Pemasyarakatan Ditinjau dari Perspektif Etika Medis dan Hukum - Sri Dwiyanti; Binner Habeahan; Muhammad Taufik Hidayah; Yeti Kurniati; Hernawati RAS (Pusat Riset dan Inovasi Nasional, 2025)
The management of HIV/AIDS cases in correctional facilities faces various challenges related to medical confidentiality, social stigma, and limited healthcare facilities. This study aims to examine the implementation of medical confidentiality in HIV/AIDS management in correctional facilities, considering both medical ethics and legal perspectives. Prisons, as detention centers that tend to be overcrowded, are high- risk environments for the spread of infectious diseases, including HIV/AIDS. The stigma associated with prisoners infected with HIV/AIDS often prevents them from accessing necessary healthcare services, further complicating their treatment. This study analyzes existing regulations concerning medical confidentiality, as well as the obstacles that arise in the practice of HIV/AIDS management in correctional facilities, with a focus on health policies and the role of medical staff in balancing confidentiality and disease prevention. The results of the study indicate that clear policies regarding the management of medical information are essential to prevent violations of prisoners' rights, as well as to facilitate more effective prevention and treatment of HIV/AIDS.